Topical Application Type of Fish Oil Promotes Re-Epithelialization in Burn Wound Healing in Rats - Sasongko, Heru; Pitaloka, Nirwana Asri Diah; Kurniawan, Muhammad Rizki; Pramono, Edi; Setyawan, Novan Adi; Rohman, Abdul (Faculty of Pharmacy, Universitas Gadjah Mada, 2025)
Burns are a condition that is often found in the world in various cases such as accidents. The incidence of burns will probably increase as human activities become more complex. Wounds that are not treated immediately tend to become infected and cause death. Fish oil is one of the ingredients that has been studied for wound healing. Previous research shows that fish oil is rich in long-chain omega-3 fatty acids such as docosahexaenoic acid and eicosapentaenoic acid, which have anti-inflammatory effects. However, there has not been much research on the type of fish oil used and the wound healing process. The aim of this study was to determine the wound-healing activity of milkfish (Chanos chanos Forsskal.), patin (Pangasius djambal), and eel (Anguilla bicolor) fish oil. Tests were carried out on 25 mice as an experimental animal model for burn wounds. Data on percent wound reduction and the re-epithelialization process were statistically calculated using one-way analysis of variance (ANOVA) followed by a post-hoc LSD test. The research results showed that milkfish oil, patin fish oil, and eel fish oil in a concentration of 10% on an ointment basis were able to reduce wounds significantly. Eel fish oil shows the greatest burn wound healing process with re-epithelialization when compared to other oils. The type of fish oil affects the wound healing process.